2007
DOI: 10.1055/s-2007-984527
|View full text |Cite
|
Sign up to set email alerts
|

Biorenewable Resources in the Biginelli Reaction: Cerium(III)-Catalyzed Synthesis of Novel Iminosugar-Annulated Perhydropyrimidines

Abstract: An unprecedented version of the Biginelli reaction using an unprotected aldose as a biorenewable aldehyde component and 2-phenyl-1,3-oxazol-5-one as a novel active methylene building block with urea/thiourea is reported. The reaction is cerium(III)catalyzed, expeditious, and effected under solvent-free microwave irradiation conditions to yield diastereoselectively, iminosugar-annulated polyfuntionalized perhydropyrimidines via ring transformation of an isolable intermediate followed by cyclodehydration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Recently, Yadav et al have reported the one-pot synthesis of 4-amino perhydropyrimidines 10 upon a Biginelli reaction. Upon microwave irradiation and in the presence of a Ce(III) salt, D-xylose and D-glucose react with ureas 8 and thioureas generating aldose-derived C¼N species that are attacked in situ by an 1,3-oxazol-5-one 9 and finally evolve to the perhydropyrimidine 10 diastereoselectively (Scheme 9.2) [9]. p-Toluenesulfinimines 11 can participate as chiral inductors in the BF 3 ÁEt 2 O-mediated addition of lithiated a-imino glycinates to afford enantiopure 4,5-trans 4-carbomethoxy N-sulfinylimidazolidines 12 (Scheme 9.2).…”
Section: Reaction Of Glycinates and Related Nucleophiles With Electromentioning
confidence: 99%
“…Recently, Yadav et al have reported the one-pot synthesis of 4-amino perhydropyrimidines 10 upon a Biginelli reaction. Upon microwave irradiation and in the presence of a Ce(III) salt, D-xylose and D-glucose react with ureas 8 and thioureas generating aldose-derived C¼N species that are attacked in situ by an 1,3-oxazol-5-one 9 and finally evolve to the perhydropyrimidine 10 diastereoselectively (Scheme 9.2) [9]. p-Toluenesulfinimines 11 can participate as chiral inductors in the BF 3 ÁEt 2 O-mediated addition of lithiated a-imino glycinates to afford enantiopure 4,5-trans 4-carbomethoxy N-sulfinylimidazolidines 12 (Scheme 9.2).…”
Section: Reaction Of Glycinates and Related Nucleophiles With Electromentioning
confidence: 99%
“…As part of our ongoing research programme and continued interest in devising new solvent-free cyclization processes [35][36][37][38][39], we had to develop an efficient synthetic approach to pyranothiazoles incorporating a thiol function at C-6. For this purpose, we utilized the mercaptoacetyl transfer agent, 2-methyl-2-phenyl-1,3oxathiolan-5-one ( Figure 1) [38], which leads to the desired mercaptoacetylative heteroannulation and is the key element in the present successful synthetic strategy for the target compounds 4 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…This easily accessible chemical has been used as building block in the synthesis of N-carbamoyl-L-amino acids, 1 cyclic carbonates, 2 and many nitrogen-containing heterocycles such as pyridines, 3 pyrimidines, 4 3,4-dihydropyrimidinones, 5 oxazines, 6 1,3-ox-azin-3-ones, 7 and iminosugars. 8 Another application of urea in carbohydrate chemistry was described earlier. 9 Urea is also employed as source of ammonia in the syntheses of triarylamines, 10 imides, 11 and amides.…”
Section: Introductionmentioning
confidence: 99%
“…(F) Iminosugars are compounds with great pharmacological importance. Yadav et al8 reported that the reaction of 2-phenyl-1,3-oxazol-5-one, urea, and unprotected aldoses following the Biginelli protocol under solvent-free conditions leads to the formation of functionalized iminosugars in good yields and high trans diastereoselectivity. (G) Recently, Artamkina et al10 developed a new method for triarylamine synthesis using a palladium-catalyzed C-N bond formation (Buchwald-Hartwig reaction).…”
mentioning
confidence: 99%